2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5627106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the chain of magnetosomes embedded in magnetotactic bacteria and their motility on Magnetic Resonance imaging

Abstract: This paper investigates the influence of the magnetosome's chain, the motility, and the bacterial cell of MC-1 magnetotactic bacteria (MTB) on the Magnetic Resonance imaging (MRI) contrast. Because of its embedded magnetic nanoparticles, that allow magnetic guidance and imaging contrast generation under MRI, magnetotactic bacteria are being considered for therapeutic drug delivery to tumors. In order to separately investigate the different potential sources of contrast in MRI, we used three samples of MC-1 MTB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Even lower numbers of magnetosome-loaded cells were readily detected by MRI. Felfoul et al (2010) investigated the influence of the magnetosome's chain and the MC-1 MTB cell on the MRI contrast and observed that magnetosomes were the predominant source of contrast in MRI over motion and the cell body. Goldhawk et al (2012) reviewed the magnetosomes as a reporter of gene expression in MRI and found that their suitability and superiority for development of reporter gene expression for MRI.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Even lower numbers of magnetosome-loaded cells were readily detected by MRI. Felfoul et al (2010) investigated the influence of the magnetosome's chain and the MC-1 MTB cell on the MRI contrast and observed that magnetosomes were the predominant source of contrast in MRI over motion and the cell body. Goldhawk et al (2012) reviewed the magnetosomes as a reporter of gene expression in MRI and found that their suitability and superiority for development of reporter gene expression for MRI.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…The possibility of using magnetosomes from magnetotactic cocci [182] and spirilla [183] as contrast agents has been established experimentally, which, in combination with effective control by means of an external magnetic field, can be used for magnetic resonance imaging (MRI) in the positive and negative contrast mode, including that in real time [181]. MRI can be used to create bacterial or hybrid medical nanorobots that can controllably move through the human circulatory system [184,185], as demonstrated in a model system based on a microfluidic chip [186].…”
Section: Application Of Magnetosomes In Biomedicine and Biotechnologymentioning
confidence: 99%
“…Enzyme immobilization and bioremediation: magnetosomes expressing MamC fused with organophosphohydrolase (OPD) from of Flavobacterium sp., were used for the degradation of paraoxon. Reprinted from [24] Acute toxicity (LD50) in rats, mg/kg 135-180 480 [146,201] Cytotoxicity (HUVEC 2 MTT assay), mg/mL 0.07-1.0 3 0.1-5.1 [176][177][178]188,189,200,202] Maximum non-hemolytic concentration, mg/mL 3.0 1.6-4.0 [176,189,208] Magnetic resonance relaxivity r 2 , mM −1 s −1 130-170 150-600 [127,182,187,189,200] Specific absorption rate, kW/g 0.6-0.8 0.4-1.4 [132,183,185,209] Minimal biodegradation period, days 30 28-42 [177,200,201,210] Magneto Immuno-PCR limit of detection, ng/mL 8 0.32 [191] DNA extraction release, µg/mg 1.0-2.2 3.0-19.2 [195] In vitro studies have shown that interaction with an alternating magnetic field allows using magnetosomes conjugated with polyclonal antibodies to bind and destroy pathogen cells, in particular Staphylococcus aureus, not via the thermal effect but through the mechanical pressure created by magnetosomes [211]. Due to the ability to biosorb metal ions from an aqueous medium, MTB can be used for environmentally safe biosynthesis of controlled size gold, silver, platinum, and palladium nanoparticles [212].…”
Section: Application Of Magnetosomes In Biomedicine and Biotechnologymentioning
confidence: 99%
“…17 Likewise, Felfoul et al tracked a cluster of magnetotactic bacteria (5x10 7 bacteria per mL) by using magnetic resonance imaging. 18 Positron emission tomography (PET) combined with X-ray computed tomography (CT) was also used to image swarms of catalytic micromotors. However, this technique required radioactive isotopes and the temporal resolution (7 frames in 15 min) was low.…”
Section: Introductionmentioning
confidence: 99%